2020
DOI: 10.1101/2020.06.18.20135210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universality in COVID-19 spread in view of the Gompertz function

Abstract: We demonstrate that universal scaling behavior is observed in the current coronavirus (COVID-19) spread in various countries. We analyze the numbers of infected people in selected eleven countries (Japan, USA, Russia, Brazil, China, Italy, Indonesia, Spain,South Korea, UK, and Sweden). By using the double exponential function called the Gompertz function, fG(x)=exp(−e−x), the number of infected people is well described as N(t)=N0 fG(γ(t−t0)), where N0, γ and t0 are the final total number of infected people, th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…Figure 5 shows that, as the CSIR model solution predicts, for each country considered, the integral of the RMM and the RCO are linearly correlated to a high degree. As orthogonal correlative support for the veracity of the CSIR solution, we note that other authors (9) have observed that the daily COVID-19 case data from many countries can be fit with a Gompertz model. Since Equation 13 is also a Gompertz equation, those observations support the assertion that Equations 10 to 13 properly model epidemics.…”
Section: Figure 3 Complete Sir (Csir) Model Predictions For Number Of New Daily Cases A) Southsupporting
confidence: 74%
“…Figure 5 shows that, as the CSIR model solution predicts, for each country considered, the integral of the RMM and the RCO are linearly correlated to a high degree. As orthogonal correlative support for the veracity of the CSIR solution, we note that other authors (9) have observed that the daily COVID-19 case data from many countries can be fit with a Gompertz model. Since Equation 13 is also a Gompertz equation, those observations support the assertion that Equations 10 to 13 properly model epidemics.…”
Section: Figure 3 Complete Sir (Csir) Model Predictions For Number Of New Daily Cases A) Southsupporting
confidence: 74%
“…While the excess peaks look highly symmetrical around their maximum and can thus be reasonably well modeled with Gaussians, as described before, the peak of the spring 2020, associated with the COVID-19 pandemic, is clearly asymmetric. We have tried several possible parametrizations for that distribution, such as bifurcated Gaussians with a common peak, generalized logistics, or else, to reflect the asymmetry, but in the end we resolved to adopt the derivative of a Gompertz function [ 19 , 20 ] simply because it is customarily adopted by epidemiologists to describe epidemic evolution’s over time and we therefore considered it more suitable to our purpose.…”
Section: Methodsology Of the Data Analysismentioning
confidence: 99%
“…Covid-19 mortality above age 20 follows everywhere the so-called Gompertz law of mortality (in which death rates can be expressed as an exponential function of age). 23 24 25 As a result of this strong mathematical regularity, death rates unknown at one given age can be extrapolated from death rates observed at other ages. Another advantage of the Gompertz modeling is its partition of mortality into two main components: its age gradient (i.e., the slope, or the tempo of mortality) that corresponds to variations by age, and its intensity (the level or quantum of mortality) that captures the overall severity at all ages.…”
Section: Mortality Estimation Strategymentioning
confidence: 99%